Chemical Interesterification of oil for the obtaining of a greasy base without greasy acids trans - Legua Cárdenas, José (2010)
The fatty acids trans form during the partial hydrogenation of oils, and is the present process that the national industrialist for the elaboration of the fat uses, for the elaboration of margarine. Studies have indicated problems in the health by the oil consumption with fatty acids trans, reason why it is required to have other alternatives of process that does not generate fatty acids trans, in the present investigation has considered as objective to obtain a greasy base for margarine without fatty acids trans, using the reaction of chemical interesterification for a mixture of oil of soya and palm, which was catalyzed with metóxido of sodium. The conditions of reaction were for the mixture of triglycerides a proportion in weight of 1:3 of oil of soya and palm, 1% in weight of catalyst and one temperature of 140ºC, that were optimal after the variance analysis, corresponded to the fourth experimental test whose results show to a good approach in the percentage of solid fat content (SFC) with the ideal curve for fat for margarine and the fusion point recommended of 35ºC, also has correlation with the results found by Liu and Scot, 2001. The chromatographic analysis was realised registering 0.4% in fatty acids trans and so the objective is fulfilled drawn up.